SENYAPAN DAN PENYEBABNYA PADA DEBAT FINAL PEMILIHAN KEPALA DAERAH KHUSUS IBUKOTA JAKARTA TAHUN 2017 - Sasmitasari, Novi; Saman, Sisilya; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to explain and elaborate the result of silence analysis and the cause in Final Debate of 2017 Regional Head Election of Special Capital Region of Jakarta. Method used was descriptive in form of qualitative. Data sources were utterances produced by the two candidate pairs of regional head of Special Capital Area of Jakarta in 2017 who did a debate in a video along with the people involved. The research data was the silence occurred in the Final debate of 2017 Regional Head Election of Special Capital Region of Jakarta. Technique of collecting data used were exposure technique and context analysis. The tool of collecting data was video record. Data analysis method used was SBLC technique ? a listening method. Based on the result, there were 80 times of silence in debate. The type of silence were content silence, quiet silence, progressive repetition, false starts, elongation, refinement, and silence combination. The silence are occurred in the beginning, middle, and ending or even the combination of these three in a sentence. Some of the cause of silence are circumspection, demanding more time, repetition, false starts, hesitation, nervousness, and refinement. This research can contribute to the learning especially in speaking aspects.                Key Words: silence, type, distribution, the cause, debate